2008
DOI: 10.2967/jnumed.108.055194
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Cardiac Sympathetic Nervous System Abnormality in the Long-Term Prognosis of Patients with a History of Ventricular Tachyarrhythmia

Abstract: Severe left ventricular dysfunction or cardiac sympathetic nervous system (SNS) abnormality predicts cardiac death in various heart diseases, including arrhythmogenic disorders. However, it is not clear whether SNS abnormality predicts sudden cardiac death during long-term follow-up in patients with a history of ventricular tachyarrhythmia. We hypothesized that SNS abnormality would be associated with recurrent ventricular arrhythmic events. Methods: 123 I-metaiodobenzylguanidine (MIBG) scintigraphy was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
(30 reference statements)
0
19
0
1
Order By: Relevance
“…Cardiac sympathetic nerve activity evaluated by 123 I-MIBG scintigraphy has prognostic value in these patients [7,8]. Moreover, recent clinical studies have suggested that 123 I-MIBG imaging predicts ventricular arrhythmias in patients with heart failure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac sympathetic nerve activity evaluated by 123 I-MIBG scintigraphy has prognostic value in these patients [7,8]. Moreover, recent clinical studies have suggested that 123 I-MIBG imaging predicts ventricular arrhythmias in patients with heart failure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation is characterized by a highly irregular ventricular rhythm, which we have shown to produce elevated sympathetic nerve activity (SNA) [3]. Elevated SNA has been shown to be directly correlated with poor prognosis and increased mortality [4,5] and, thus, it is suggested that the ventricular irregularity during AF increases the risk for SCD by a baroreflex-mediated sympathoexcitation [6].…”
Section: Paradox Of Autonomic Effects During Atrial Fibrillationmentioning
confidence: 98%
“…Akutsu, et al 27) also evaluated 86 patients with a history of ventricular tachycardia or fibrillation who were followed for approximately 11 years. They concluded that a low H/M ratio was associated with sudden cardiac death or recurrent ventricular tachyarrhythmic events (P = 0.004) in these patients.…”
Section: I-mibg Scintigraphymentioning
confidence: 99%